Challenges of ICT Integration in Social Work Practicums in African Higher Education: A Systematic Review - Rammutla, Mmathato Calphurnia (Innovation Journal of Social Sciences and Economic Review, 2024)
This systematic review explores the role of Information and Communication Technology (ICT) in enhancing social work practicums within higher learning institutions across developing African nations. Key challenges identified include the absence of clear institutional policies for ICT integration, insufficient funding for welfare organizations, particularly from the South African Department of Social Development, and unreliable internet access in rural regions. Additionally, the lack of clarity within the Department of Education’s policy framework regarding appropriate technologies for educational curricula hinders students’ practical experiences. Using the PRISMA methodology, this review analyzed 65 peer-reviewed articles selected from an initial retrieval of 320 sources from databases such as Google Scholar, Taylor & Francis, Scopus, ScienceDirect, and ResearchGate. The inclusion and exclusion criteria ensured relevance to the topic of ICT challenges in social work education. The findings highlight a pressing need for revised policies and the introduction of new legislation to address the technological barriers that limit social work students’ access to essential resources like Wi-Fi, digital infrastructure, and institutional support. These challenges are particularly acute in South Africa, Zimbabwe, and Mozambique, where limited technological infrastructure and financial constraints impede progress. Nonetheless, the development of Continuing Professional Development (CPD) guidelines, the introduction of affordable technologies, and the establishment of a robust national policy framework for ICT integration can significantly improve the quality of social work practicums, facilitating better alignment between theory and practice.